Analisis Ukuran Perusahaan, Roi Dan Dar Terhadap Ketepatan Waktu Penyampaian Laporan Audit: (Studi Kasus Pada Perusahan Lq45 Yang Terdaftar Di Bei Tahun 2017 - 2019) - Endang Dwi Wahyuningsih; Aniqotunnafiah Aniqotunnafiah; Lusi Permata Putri (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aims to analyze the influence of company size, ROI and DAR on the timeliness of submitting audit reports to LQ45 companies listed on the IDX for the 2017-2019 period. The population in this research is all companies included in the LQ45 Index from 2017 to 2019, a total of 135 companies. This research uses quantitative methods with secondary data and logistic regression data analysis techniques. The results of this research show that ROI and DAR have no effect on the timeliness of submitting audit reports. Meanwhile, company size has a significant effect on the timeliness of submitting audit reports